Impact of MSME Assistance Program by East Java Province to Resolve the Economic Impacts of Covid-19 - Agus Adriyanto; Maryanti Maryanti; Kukuh Setyo Pambudi (Yayasan Ilomata, 2021)
This paper aims to provide a perspective on assistance to MSMEs in East Java in the face of the Covid-19 pandemic. So far, MSMEs have been proven to be one of the economic drivers that accommodate the majority of workers in Indonesia. The existence of the Covid-19 Pandemic has depressed MSMEs throughout Indonesia and often have to go out of business. It seems that the government assistance that has been provided in the context of Covid-19 is still focused on individual or family assistance. Therefore, the authors consider MSMEs to be an essential factor in efforts to overcome the impact of Covid-19, especially in East Java. This paper uses the review literature as a method of data collection and research. The research results are expected to be an input for the Government, especially East Java Province, to consider the existence of capital assistance for MSME’s.